Internet of Things for Food Sector: Status Quo and Projected Potential. Issue 6 (17th August 2020) - Kodan, Rahul; Parmar, Puneet; Pathania, Shivani
ABSTRACT: Internet of Things is one of the most bustling terminologies throughout the world presently. This paper aims at exploring, perceiving, learning, and sensitizing readers, especially those who are directly or indirectly connected to the field of food and agriculture, about various current applications and future opportunities associated with Internet of Things. The concept of Internet of Things is gaining popularity due to its close association with one of the most revolutionary human discoveries, the Internet, and also due to the opportunities in ease of living provided by various applications of the concept. In this paper, all the current developments and future prospects of this concept in food and agriculture sector have been discussed, which will bring more clarity on the practicality of the concept. This paper aims at providing more conformity on the concept of Internet of Things and its applications in food and agriculture.